Eksistensi Surat Kabar Media Indonesia di Era Digital - Apriansyah Apriansyah; Helmi Fithriansyah; Teguh Rahadian (Populis : Jurnal Sosial dan Humaniora, 2023)
Competition in the media industry today is increasingly competitive. Competition is often an important factor in improving the performance of a media in maintaining its existence in the competition between media. The print media industry is faced with a variety of obstacles, ranging from high production and distribution costs to advances in information communication technology. The ability to adapt and innovate is needed to avoid the displacement of print media in the mass media industry. This research was conducted on Media Indonesia as a print-based conventional media industry that continues to strive to maintain its existence in the midst of the rapid presence of new media. This research uses the theory of Media Economics as originated by Robert Pickard, Media Economics is a study of how the media as an industry utilizes limited resources to produce and distribute content or content to audiences that aims to meet demands and needs. Through the interview method, information on what obstacles are currently faced in the media industry, especially print, can be confirmed. The high cost of production and distribution, changes in people's culture in seeking and consuming information and advances in communication information technology are also obstacles that must be taken seriously by industry players in print media.Kompetisi pada industri media saat ini semakin kompetitif. Kompetisi seringkali menjadi faktor penting dalam meningkatkan kinerja sebuah media dalam mempertahankan eksistensinya di persaingan antar media. Industri media cetak dihadapkan pada beragam kendala, mulai dari mahalnya biaya produksi dan distribusi hingga kemajuan teknologi informasi komunikasi. Kemampuan beradaptasi dan berinovasi diperlukan untuk menghindari tergusurnya media cetak dalam kancah industri media masa. Penelitian ini dilakukan terhadap Media Indonesia sebagai industri media konvensional berbasis cetak yang terus berupaya mempertahakan eksistensinya di tengah derasnya kehadiran media baru. Penelitian ini menggunakan teori Ekonomi Media sebagaimana dicetus Robert Pickard, Ekomoni Media merupakan studi yang mempelajari bagaimana media sebagai industri memanfaatkan sumber daya yang terbatas untuk memproduksi dan mendistribusikan isi atau konten kepada khalayak yang bertujuan untuk memenuhi permintaan dan kebutuhan. Melalui metode wawancara, informasi mengenai kendala apa saja yang saat ini dihadapi dalam industri media terutama cetak bisa dikonfirmasi. Mahalnya biaya produksi dan distribusi, perubahan budaya masyarakat dalam mencari dan mengkonsumsi informasi serta kemajuan teknologi informasi komunikasi juga menjadi kendala yang harus disikapi secara serius oleh pelaku industri di media cetak.